Achievement-Related Shame and Guilt in Elementary Students: A Pilot Study - Kirsty Choquette (Canadian Society for Studies in Education, 2023)
Children can experience shame or guilt in response to academic failure. However, most of the research on achievement-related shame and guilt has been conducted with adult learners. The implications these emotions may have for children's learning necessitates further research to understand achievement-related shame and guilt in young students. In this pilot study, I investigated whether (a) children feel increased shame and guilt after an academic failure, (b) these emotions were related to ability and effort, and (c) the relationships were mediated by perceptions of the cause's locus and controllability. While students did feel increased shame and guilt after a failure, the relationships between these emotions and students' cognitions about the causes of their failure differed from those found in research with adults. These findings suggest further research and theorizing is needed to understand students' feelings of achievement-related shame and guilt so educators and caregivers can promote young students' long-term success.